Financializing Chinese cities: state–capital nexus and the uneven geography of housing speculation. Issue 4 (2nd October 2019) - Lin, George C.S.; Smart, A.; Li, X.; Hu, Fox Z.Y.
ABSTRACT: Current enquiries into the transformation of cities from 'growth' to 'debt machines' are largely based on studies of selected European and American cities where municipal governments temporally repackaged and rescheduled current fiscal problems by selling off city futures. This study of a recent episode of housing speculation in urban China identifies a distinctive trajectory in which the state has reshuffled financial resources sectorally and spatially. A misallocation of resources into the real estate sector and into a few top-tier cities fuelled a speculative housing market in a context of slowing economic growth. In contrast to external and horizontal public–private partnerships in American cities, coalitions of speculative urbanism in China involved vertical and hierarchical relationships internal to state power. This research calls for a broadened theoretical attention to the changing and variegated nature of the interrelationships between state, capital and space.